PELATIHAN PENGOLAHAN DATA MAHASISWA AKUNTANSI UNIVERSITAS BUMIGORA DENGAN SMARTPLS 4.0 - Ika Putri Fitri Ajiani (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
This community service initiative aims to prepare early-semester students to face increasingly complex data processing challenges in their upcoming semesters. The data processing mentoring was conducted over one month, consisting of four online face-to-face sessions. The data used as a processing example focused on the influence of accounting knowledge, economic motivation, and gender on students' interest in pursuing a career as a public accountant. The participants of this training consisted of 50 accounting students from Bumigora University. The software utilized for this training was the SmartPLS 4.0 application. The success of this program was demonstrated by the analysis reports generated by the students based on their processed data. The success rate of student comprehension in this training was 88%. This community service is expected to be highly beneficial for students when writing their undergraduate theses.